Learning path : doing data visualization. - Fhala, Ben; Hombergs, Tom; Simoes, Alex; Westbay, Michael; Teller, Swizec; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2016)
"You've collected your data, undertaken a preliminary analysis, and now you need to communicate your findings to the world. In this Learning Path you'll discover how you can utilize the power of the modern web to communicate complex concepts and ideas as simple and easily digestible interactive visualizations."--Resource description page.
Mastering HTML5 canvas / Ben Fhala -- Web visualization with HTML5, CSS3, and JavaScript / Ben Fhala -- Rapid highcharts / Tom Hombergs -- Building interactive data visualizations with D3.js / Alex Simoes, Michael Westbay -- Mastering D3.js / Swizec Teller.
Presenters, Ben Fhala, Tom Hombergs, Alex Simoes, Michael Westbay, Swizec Teller.
Title and publication information from resource description page (Safari, viewed July 11, 2016).
Keywords: Information visualization; Web applications -- Development; Web site development; Electronic books